2021
DOI: 10.1007/jhep10(2021)184
|View full text |Cite
|
Sign up to set email alerts
|

An equation-of-state-meter for CBM using PointNet

Abstract: A novel method for identifying the nature of QCD transitions in heavy-ion collision experiments is introduced. PointNet based Deep Learning (DL) models are developed to classify the equation of state (EoS) that drives the hydrodynamic evolution of the system created in Au-Au collisions at 10 AGeV. The DL models were trained and evaluated in different hypothetical experimental situations. A decreased performance is observed when more realistic experimental effects (acceptance cuts and decreased resolutions) are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Later, this strategy was deepened in a series of studies for more realistic scenarios, e.g., to take into account the afterburner hadronic cascade by incorporating UrQMD following the hydrodynamics evolution [85,86]; to consider non-equilibrium dynamics of the phase transition's influence, e.g., spinodal decomposition [18,87] or Langevin dynamics [88]; to include more realistic experimental detector effects through detector simulation with hits or tracks as the input [48,89]; to perform unsupervised outlier Fig. 9 Evolution history of QGP simulated using the relativistic hydrodynamic model CLVisc, starting from the same initial condition with four different parameter combinations.…”
Section: Crossover or First-order Phase Transitionmentioning
confidence: 99%
“…Later, this strategy was deepened in a series of studies for more realistic scenarios, e.g., to take into account the afterburner hadronic cascade by incorporating UrQMD following the hydrodynamics evolution [85,86]; to consider non-equilibrium dynamics of the phase transition's influence, e.g., spinodal decomposition [18,87] or Langevin dynamics [88]; to include more realistic experimental detector effects through detector simulation with hits or tracks as the input [48,89]; to perform unsupervised outlier Fig. 9 Evolution history of QGP simulated using the relativistic hydrodynamic model CLVisc, starting from the same initial condition with four different parameter combinations.…”
Section: Crossover or First-order Phase Transitionmentioning
confidence: 99%
“…Moreover, the analysis was recently extended to directly use the experimental detector readout, where the PointNet-based model was accordingly explored to identify the QCD transition type for the Compressed Baryonic Matter experiment. [50] 6. EoS Study from HICs.…”
Section: -3mentioning
confidence: 99%
“…Due to their abilities to capture complex nonlinear correlations in data, deep learning techniques have been proven useful in solving a number of physical problems, e.g. determining the parton distribution function [39,40], reconstructing the spectral function [41][42][43], identifying phase transitions [44][45][46][47][48][49], assisting lattice field theory calculations [50][51][52][53], evaluating centrality distributions for heavy ion collisions [54][55][56], parameter estimation under detector effects [57,58], and speeding up hydrodynamic simulations [59]. Earlier works that incorporated DL methods have shown that DNNs can potentially surpass traditional methods in solving inverse design problems [60][61][62].…”
Section: Reconstructing the Eos Via Automatic Differentiationmentioning
confidence: 99%